Southeast Asia in the US rebalance : perceptions from a divided region - Graham, Euan (2015)
This article explores perceptions and reactions across Southeast Asia towards the Obama administration’s “pivot” or “rebalance” to Asia. The US approach has been dismissed as more rhetorical than substantive grand strategy, its credibility under renewed scrutiny following President Obama’s cancelled visit to Southeast Asia in October 2013. Nonetheless, the rebalance has expanded from its origins in 2010–11, acquiring diplomatic and economic “prongs” with a particular focus on Southeast Asia, broadening the bandwidth of US engagement beyond military diplomacy and force realignment. However, the US “pivot” has had to contend with entrenched narratives of the US role in the region oscillating between extremes of neglect or over-militarization. The US-China strategic dynamic weighing over the region, itself central to Washington’s strategic calculus across Asia, has also coloured the lens through which Southeast Asians have viewed the re-balance. Varied reactions to the US rebalance at the national level in Southeast Asia are further suggestive of a sub-regional divide between “continental” and “maritime” states that to some extent predisposes their perspectives and orientation towards the Great Powers.